‘Den Gamle’ som præst eller et blik ind i N. F. S.Grundtvigs præstevirke især i perioden efter sygdommen 1867 - Eskedal, Anders (Grundtvig-studier, 2003)
‘ Den Gamle * som prast eller et blik ind i N. F. S.Grundtvigs prastevirke isar i perioden efter sygdommen 1867[‘ The Old Man ' as Priest, or, a Glimpse into N. F. S. Grundtvig's Ministry especially in the Period Following the Illness of 1867]By Anders Eskedal Despite the infirmities of old age, Grundtvig continued right up to his death to serve as priest in Vartov Church. All who have given any account of these church services agree that they were a moving experience. This was not because of the sermons, from which perhaps only a small minority could fully profit, but rather because of the whole atmosphere surrounding the services. The old bishop was certainly a charismatic figure but the centre-point was the hymn-singing and prayer and the solemnity of the sacraments; and the fellowship of the Vartov congregation was no mere figure of speech.Vartov was not a parish church, and the congregation which gathered about Grundtvig came from the whole of Copenhagen - sometimes, indeed, from far beyond. But from out of Vartov and its divine service inspiration went forth to the Grundtvigian congregations all across the land.This inspiration emanated also from the Friends’ Meetings which functioned from 1863 as annual conventions of the Grundtvigian movement. Here were discussed matters of importance to the movement and here they met ‘the Old Man’ who would typically hold divine service, make an address and answer questions.His third wife, Asta, would keep open house at home so that Grundtvig, who was otherwise not good at making connections, could now come into personal contact with many of those who had previously known him only through his books; indeed, he began himself to issue invitations.In the last years of his life he oversaw the second editions of some of his most important books, among others the Sangvark [Song-work (or Carillon) for the Danish Church] from 1837. The most significant new publication was doubtless the ecclesiastical-historical lectures Kirke-Speil [Mirror of the Church] from 1870.Grundtvig’s health had always been sturdy but from about 1860 he began to have difficulty walking because of ‘rosen’ (erisypelas) and fluid in the legs. After the major breakdown in 1867 he was noticeably enfeebled. He began also to suffer from deterioration of his eyesight which in the end rendered him almost blind, so that his sermons had to be written out in big latin characters and books and newspapers had to be read aloud to him. But his brain and especially the elephantine memory continued unenfeebled.He died on 2 September 1872, a week before his 89th birthday.